Frying kinetics and physical properties of air-fried french fries - Hawa, La Choviya; Izzati, Syifa Rahadian; Yulianingsih, Rini; Nugroho, Wahyunanto Agung (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
French fries are processed products made of partially cooked frozen potatoes. The most essential step in making french fries is frying, aiming to produce soft and crunchy product. Using air fryers in the frying process offers the benefit of significantly reducing oil consumption, thereby making it a favorable option for producing lower-fat fried foods. The objectives of the present study were to analyze the physical and chemical characteristics of french fries on the use of oil and time variation in the air frying method and to determine the frying kinetics under the air fryer. Finding the best frying method was carried out using some attributes of Zeleny, such as the frying rate. Frying was controlled at a constant temperature of 180 °C with time variations of 10, 13, and 16 minutes, and variation in the amount of oil, i.e., 2 mL, 4 mL, and without oil. The results showed the physical characteristics of french fries that include moisture content (26.85 – 45.56%), color with indicators L* (64.44 – 68.66), a* (0.01 – 4.80), b* (21.32 – 35.54), color differences (4.57 – 10.60), hardness (120.83 – 559.8 g), springiness (1.15 – 2.82 mJ), chewiness (0.33 – 3.98 mm), gumminess (28.6 – 213.43 g), and cohesiveness (0.2 – 0.41). The variations in the amount of cooking oil in the air frying method significantly affect the redness parameters. The time variation in the air frying method significantly affects moisture content, hardness, gumminess, chewiness, and cohesiveness parameters. Lightness, yellowness, colour differences, and springiness parameters have no significant effect on the variation of oil and time. The chemical characteristic of french fries includes fat content (5.78 – 22.42 %). The air frying method without oil used for 13 minutes was considered as the best treatment for frying french fries.